Public Benchmarking: contributions for subnational governments and Benchmarking Design - Del Giorgio Solfa, Federico (2017)
The theme of this book is benchmarking in the public sector and part of the interest to analyze the importance that benchmarking has gained in the sector -as a tool for improvement and innovation of public management- where States commit efforts to achieve quality, efficiency and effectiveness in the services it provides. The study is exploratory and descriptive, employing a qualitative methodology that combines a bibliographic analysis for the elaboration of the theoretical framework and the definition of the types and dimensions of benchmarking, with the identification and description of experiences from the empirical evidence surveyed. In a special chapter, the importance, scope and dimensions of benchmarking of product design (comparative evaluation of product design or industrial design) is discussed for the state assessment in design and development of new products for micro, small and medium producers. Our approach includes the different policies and actions to support Micro, Small and Medium Industries (MiPyMIs), which are undertaken from subnational states.